2007
DOI: 10.1093/jaoac/90.2.437
|View full text |Cite
|
Sign up to set email alerts
|

Fast Cleanup Method for the Analysis of Sudan IIV and Para Red in Various Foods and Paprika Color (Oleoresin) by High-Performance Liquid Chromatography/Diode Array Detection: Focus on Removal of Fat and Oil as Fatty Acid Methyl Esters Prepared by Transesterification of Acylglycerols

Abstract: A fast and effective cleanup method was developed for the analysis of Sudan I, II, III, IV, and Para Red (Sudan dyes) in various foods and paprika color (oleoresin) by high-performance liquid chromatography (LC) with a diode array detector (DAD). Removal of fat or oil in fatty sample was a critical point for reducing the volume of the final sample solution in order to obtain a sufficient level of the analytes. Separation of fat or oil from the dyes with a silica gel solid-phase extraction (SPE) column seemed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Para Red is an azo dye used in printing that is chemically similar to Sudan I ( Fig. 1) [17]. Sudan I is a liver and urinary bladder carcinogen in mammals and considered a possible human mutagen [3,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Para Red is an azo dye used in printing that is chemically similar to Sudan I ( Fig. 1) [17]. Sudan I is a liver and urinary bladder carcinogen in mammals and considered a possible human mutagen [3,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…HPLC Model (Dionex Instruments, USA) with version 6.8 chromeleon software was using to record the absorption spectra of the Sudan dyes as the method described by ( Uematsu et al 2007) .The sudans I, II, III, and IV in chili-and curry-containing foodstuffs are extracted from the samples with dichloromethane. Sample extracts are filtered and analyzed by reverse phase HPLC using a 3.6 pH Acetonitiril or methanol (Puoci et al2005).…”
Section: Methodsmentioning
confidence: 99%
“…For example, it is reported that the relatively old and imprecise method of qualitative thin layer chromatography (TLC) is still used by the UK Food Standards Agency to detect Sudan dyes in food products (Oco and Egroodt, 2006;Genualdi et al, 2016). A similar but more advanced method involving diode array detection (DAD), conversion of the oil to FA methyl esters and further purification by silica gel chromatography has also been used successfully (Uematsu et al, 2007). However, both methods have limitations, namely the inability to simultaneously detect Sudan I-IV and the inability to quantify the presence of Sudan dyes.…”
Section: Sudan Adulteration In Palm Oilsmentioning
confidence: 99%